PEMANFAATAN MULTIMEDIA DALAM PEMBELAJARAN TRIGONOMETRI UNTUK PEMEROLEHAN KECAKAPAN INTELEKTUALDI KELAS X SMA NEGERI 1 SUNGAI RAYA - Rufini, Rufini (Universitas Tanjungpura, 2014)
This research aim to to increase activity and result of learning student by exploiting multimedia in course of learning to teach in SMA Country 1 Great River. Peculiarly this research aim to 1) Analyzing how far Acquirement learn the student in intellectual efficiency domain at trig items after taught with the exploiting multimedia 2) Mendeskripsikan Respon student of at trig items after taught with the exploiting multimedia 3) Mendeskripsikan of Pattern aktifitas learn the student of at trig items after taught with the exploiting multimedia.Hereinafter pursuant to research result indicate that the exploiting multimedia in course of mathematics study of at trig items can improve the activity and result of learning student. With the active student percentage 51,51 %, complete percentage result of learning 78,78% and percentage of is make-up of motivation and also enthusiasm learn the student 96,9 % by respon is positive pertained by a goodness. recommend from this research 1) Pursuant to research finding that exploiting multimedia in study of mathematics of trig items very effective, is therefore suggested for all education ladder exploit the multimedia in course of learning to teach 2) If we like to create the atmosphere learn more voluptuous exploit the lah multimedia in course of learning to teach 3) Expected to school head to can to equip, providing facility of related to study media of so that can be used at process learn to teach at school. Key words: Multimedia, trigonometri, activity learn the student, respon of student and achievement learn student.